2011
DOI: 10.1111/j.1465-3362.2011.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic stress disorder, depression and suicidality in inpatients with substance use disorders

Abstract: Patients entering treatment for SUDs should be assessed for PTSD, depression and suicidality. These conditions impact significantly on treatment outcomes, and require the development of appropriate treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 26 publications
10
53
2
Order By: Relevance
“…In contrast to some [3], but in agreement with others [5,32], the positive PTSD screening in our patients did not differ by gender and there were no differences regarding principle substances of concern and number of substances used. While these differences cannot be explained at present, methodological differences may play a role, since our data rely on retrospective self-report.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast to some [3], but in agreement with others [5,32], the positive PTSD screening in our patients did not differ by gender and there were no differences regarding principle substances of concern and number of substances used. While these differences cannot be explained at present, methodological differences may play a role, since our data rely on retrospective self-report.…”
Section: Discussionsupporting
confidence: 85%
“…Although it may be argued that assessing trauma/ PTSD during early detoxification treatment possesses a risk of over-diagnosing PTSD due to the substantial overlap between symptoms of withdrawal and PTSD [13,37], our results include support for the validity of the early assessment of trauma and PTSD by replicating some well-established associations from previous studies assessing trauma/PTSD mainly in abstinent patients [3,35,36]: PTSD patients had significantly higher PTSD symptoms in all domains, that is, re-experiencing, avoidance, hyperarousal [3], and significantly higher values for depression and general psychopathological burden [32]. In contrast to some [3], but in agreement with others [5,32], the positive PTSD screening in our patients did not differ by gender and there were no differences regarding principle substances of concern and number of substances used.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, 38.3% of the sample met criteria for a probable PTSD diagnosis. This is consistent with existing research demonstrating that addiction treatment-seeking individuals with SUDs are a highly traumatized population (Dore, Mills, Murray, Teesson, & Farrugia, 2012;Hien, Nunes, Levin, & Fraser, 2000;Wasserman, Havassy, & Boles, 1997).…”
Section: Descriptive Statisticssupporting
confidence: 91%
“…Posttraumatic stress disorder (PTSD) has been found to co-occur with substance use disorders, and when co-morbid, results in more negative treatment outcomes (3550). Research has found particularly high comorbidity between PTSD and opioid use disorders, relative to alcohol and other drugs (44,51,52).…”
Section: Introductionmentioning
confidence: 99%